Transcriptome Analysis of Cryptolestes ferrugineus under Low-temperature Stress - WU Tian-yi; WU Yi; FANG Zhi-yi; ZHANG Xiao-pei; WANG Fu-ling; XUE Ding-rong (Liang you shipin ke-ji)
Cryptolestes ferrugineus, a cosmopolitan stored-grain pest, was studied using transcriptome sequencing to investigate its molecular response to low-temperature stress.. Combining PacBio Iso Sequencing and Illumina RNA Sequencing, 10,508 full-length transcripts were obtained, with 9,523 successfully annotated. Compared to the control group, 477 genes exhibited significant differential expressed under low-temperature stress, including 177 upregulated and 300 downregulated genes. KEGG analysis revealed that differentially expressed genes were primarily enriched in metabolic pathways, fatty acid biosynthesis, and secondary metabolite biosynthesis. RT-qPCR was used to analyze the expression levels of six differentially expressed genes: heat shock protein, fatty acid synthase, chitinase, trehalose transporter, cytochrome P450, and vitellogenin.. The results demonstrated consistency between RT-qPCR and transcriptome sequencing analysis. This study offers preliminary insights into the molecular mechanisms of C. ferrugineus adaptation to low-temperature stress, forming a foundation for applying low-temperature grain storage technology in integrated pest management strategies.